2014
DOI: 10.3892/etm.2014.1783
|View full text |Cite
|
Sign up to set email alerts
|

BCL11A gene DNA methylation contributes to the risk of type 2 diabetes in males

Abstract: BCL11A is a critical modulator involved in hemoglobin switching. Recent studies have established an association between BCL11A gene polymorphisms and a risk of type 2 diabetes (T2D). The aim of the present study was to assess the correlation between BCL11A DNA methylation and T2D. A total of 48 T2D cases and 48 age- and gender-matched controls were recruited to evaluate BCL11A methylation using bisulfite pyrosequencing technology. Although no significant association was observed in BCL11A methylation between T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 39 publications
0
28
0
Order By: Relevance
“…Indeed, common variants in this gene have previously been associated with an increased risk of type 2 diabetes and with altered pancreatic islet hormone secretion [ 37 , 66 - 68 ]. Additionally, Tang and co-workers [ 69 ] recently showed that blood cells from males with type 2 diabetes had increased methylation of BCL11A compared with healthy male controls. In the present study, we found increased DNA methylation and decreased mRNA expression of BCL11A in male compared with female pancreatic islets.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, common variants in this gene have previously been associated with an increased risk of type 2 diabetes and with altered pancreatic islet hormone secretion [ 37 , 66 - 68 ]. Additionally, Tang and co-workers [ 69 ] recently showed that blood cells from males with type 2 diabetes had increased methylation of BCL11A compared with healthy male controls. In the present study, we found increased DNA methylation and decreased mRNA expression of BCL11A in male compared with female pancreatic islets.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the mTOR gene set, the MTOR gene is itself an intellectual disability gene that has been intimately linked to brain development 84,85 . Regarding the cholesterol metabolism gene set, the brain contains approximately 25% of the body's cholesterol (mostly as a component of the myelin sheaths that surround axons) 86,87 with defects in brain cholesterol metabolism being linked to central nervous system disease 88,89 , and BCL11A has recently been shown to influence (and be influenced by) lipid levels [90][91][92] . Furthermore, the cholesterol metabolism and mTOR gene-set enrichments may be related, as mTOR has been linked to cholesterol metabolism 93 , including in the developing brain 94 .…”
Section: Analysis Of 46 Diseases and Complex Traitsmentioning
confidence: 99%
“…All oligomers were synthesized by Sangon Biotech Co., Ltd. (Shanghai, China). Detailed information on the methylation assay has been provided in previous studies ( 15 , 16 ).…”
Section: Methodsmentioning
confidence: 99%
“…Primarily, DNA methylation, which is one of the most studied epigenetic modifications, is affected by several environmental factors, such as the diet ( 12 ), hyperglycemia ( 13 ) and hyperlipemia ( 5 ). There is that aberrant DNA methylation of pancreatic and duodenal homeobox 1 ( 13 ), monocyte chemotactic protein 1 ( 14 ), B-cell lymphoma/leukemia ( BCL11A ) ( 15 ) and glucokinase ( GCK ) ( 16 ) genes are associated with the risk of T2D. Furthermore, aberrant DNA methylation can alter gene expression ( 17 ).…”
Section: Introductionmentioning
confidence: 99%